A Fixed Point Theorem in Multiplicative Metric Space Based on Common EA-Like Property - Katta, Mallaiah; Veladi, Srinivas (Communications in Mathematics and Applications, 2022)
In the present paper, we prove the existence of a common fixed point theorem with the new structure of contractive condition in multiplicative metric space for four self maps. In this result, we use weaker compatible conditions like weakly compatible mappings and common EA-like properties. Furthermore, it is observed that non-compatible self-maps of multiplicative metric space satisfy the EA properties and weakly compatible mappings. Eventually, weakly compatible mappings and EA properties are independent of each other. Further, the outcome of this theorem will extend and generalize the existing results of multiplicative metric space. At the beginning of this paper, we discuss some basic definitions and examples which are useful for our main theorem. At the end of this paper, some examples are discussed to validate our result.
Keywords: Multiplicative metric space; Weakly compatible mappings; Common EA-like property